FROM PAGE TO SCREEN: AN ECRANIZATION STUDY OF ‘LITTLE WOMAN' - Taufik, Muh.; Nasrum, Nasrum; Nuranisa, Nuranisa (Journal of Islamic Culture and Literature (JICeL), 2023)
This research aims to describe the process of ecranization of the plot, character, and setting, in the form of categorizing aspects of reduction, addition, and changes varies. This research used descriptive qualitative and used theory of George Bluestone to analyze the reduction, addition, and changes varies in ecranizationstudy. The data collections of this research are plot, character, and setting of novel Little Women which was published in 1868 and the film Little Women which was released in 2019. In collecting data, the researcher used note taking as the instrumentto find out the reduction, addition, and changes varies of novel into film. In this research found that there are changes in the ecranization process. In the novel there isa change in reduction in 3 characters, reduction in 6 plots, and reduction in 1 setting. Whereas in the film there are changes to the addition of 2 characters, additions to 21 plots, and additions to 3 settings. Variation changes also occur in 2 characters and 2 plots but the settings are not found. The conclusion of this research is that the changes that occur in this ecranization process because the director does reduction, addition, and changes varies only to give the audience a climax and a more interesting storyline.